CUSTOMER SATISFACTION STUDY OF MEENAKSHI METAL FORMS - Kumawat, Komal; Satsangi, Priya; Sharma, Bhawana (International Journal of Engineering Technologies and Management Research, 2025)
This study examines customer satisfaction at Mennakshi Metal Forms using secondary data sources only, as no primary survey or interviews were conducted. The research aims to understand general customer expectations, common satisfaction factors, and potential improvement areas relevant to metal forming companies. Information was collected from company materials, industry reports, online customer reviews, and previous research studies. Findings suggest that product quality and pricing are key strengths typically associated with firms like Mennakshi Metal Forms, while communication, delivery consistency, and customer service are common areas requiring improvement in the metal forming sector. This paper provides insights and recommendations based on existing literature and secondary data to help enhance customer satisfaction and business performance. Keywords: Customer satisfaction, secondary data, metal forming industry, service quality, Mennakshi Metal Forms